Antioxidants: Reviewing the chemistry, food applications, legislation and role as preservatives - Carocho, Márcio (2018)
Food antioxidants play a critical role in the food industry, and have become one of the most widespread methods of conserving food. Their cheapness and ease of use have made them a part of virtually all foodstuffs. Although different, all groups of food antioxidants have a same common objective, to conserve food for the longest possible time without altering it, conferring taste or color. Consumer trends have shifted the industry to find natural antioxidants for conservation, and although synthetic additives have been the mainstream, their natural counterparts have been gaining interest. Scope and approach This review focuses of the different antioxidant groups, describing their properties, function and applicability, as well as indexing the relevant legislation in order to be a guide for academia and industry. Key findings and conclusions The wide number of antioxidant additives allowed by the different countries if of synthetic origin, and consist of pure molecules. Although consumers are leaning toward natural additives, this offer is still quite limited despite the permission of rosemary extract within the European Union. There is still much work to be done in order to completely demystify the importance and safety of antioxidants as well as to harmonize legislation worldwide.